2018
DOI: 10.1016/j.ijpddr.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and transcriptomic alterations in Leishmania donovani lines experimentally resistant to antileishmanial drugs

Abstract: Leishmaniasis is a serious medical issue in many countries around the World, but it remains largely neglected in terms of research investment for developing new control and treatment measures. No vaccines exist for human use, and the chemotherapeutic agents currently used are scanty. Furthermore, for some drugs, resistance and treatment failure are increasing to alarming levels. The aim of this work was to identify genomic and trancriptomic alterations associated with experimental resistance against the common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
65
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 116 publications
(161 reference statements)
7
65
1
5
Order By: Relevance
“…Similar results were observed following the overexpression of BCAT, although there was no additive effect when BCAT and D-LDH were coexpressed in the same line. The authors proposed that the enzymatic modification of amino or hydroxyl groups on the antibiotics could contribute to the resistance mechanisms of BCAT and D-LDH (15). In the present study, the levels of 2-keto-3-methylvaleric acid (KMVA), the 2-keto acid derivative of isoleucine, indicated increased BCAT activity in the Sb i PMM r strain compared to that in the corresponding WT.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Similar results were observed following the overexpression of BCAT, although there was no additive effect when BCAT and D-LDH were coexpressed in the same line. The authors proposed that the enzymatic modification of amino or hydroxyl groups on the antibiotics could contribute to the resistance mechanisms of BCAT and D-LDH (15). In the present study, the levels of 2-keto-3-methylvaleric acid (KMVA), the 2-keto acid derivative of isoleucine, indicated increased BCAT activity in the Sb i PMM r strain compared to that in the corresponding WT.…”
Section: Discussionsupporting
confidence: 48%
“…Leishmania species do not encode LDH, but genes for malate dehydrogenases (MDH) and a putative D-lactate dehydrogenase (D-LDH) are present. Recently, the upregulation of D-LDH and BCAT mRNA was linked to PMM r in L. donovani by transcriptome sequencing (RNA-seq) analysis of WT and PMM r strains (15). Overexpression of the putative D-LDH in L. donovani, L. major, and L. infantum also increased PMM resistance, and there was cross-resistance with other aminoglycosidic antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A proteomic approach was elected to address these issues in the present study. Although RNA sequencing and transcriptomic analysis have been extensively used to explore molecular alterations that might be associated with drug resistance in Leishmania species [29], such methodology was not employed in this work. This is because post-transcriptional regulations (via microRNAs and other non-coding small RNAs) appear to substantially change the genetic information processing from messenger RNA to protein [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study we focused on a large-scale analysis of putative gene conversion events using publicly available datasets. Previous population study of L. donovani suggested that population variability of L. donovani is fairly low, however the authors used masking procedures and strict read selection criteria [14,32]. We decided to reanalyze DNA-seq data without masking sequences, because we were interested in the most dynamic fraction of the genome.…”
Section: Introductionmentioning
confidence: 99%